Anestezjologia i intensywna terapia PiCCO a new concept of continuous cardiac output monitoring – new possibilities - Szurlej, Dariusz; Toczek, Krzysztof; Żurek, Paweł; Węglarzy, Andrzej; Machej, Leszek; Paradowski, Krzysztof; Daszkiewicz, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2005)
A Swan-Ganz catheter remains a gold standard in hemodynamic monitoring despite its presence on the market since the early 70s. It is an invasive procedure combined with a certain risk and cost. That is why some investigators keep searching for less invasive techniques. The PiCCO method is a technique which combines thermodilution and computer analysis of arterial blood pressure curve. Such a technique enables readings of cardiac output, contractility and estimates preload and after load very accurately. New possibilities like estimation of lung water are also measured and are easy to interpret on a clinical basis.